Penguatan Kapasitas Mahasiswa Melalui Kompetensi Softskill Public Speaking Bagi Pendidik PAI di Era Milenial - Moh. Faizin; Nadian Nur Afnia; Abdillah Rosyid Tamimi; Muhammad Zainul Arifin (Cendekia, 2023)
This study aims to identify, describe, and analyze the non-academic abilities of PAI students as prospective educators. In this millennial era, preparation is needed to improve the quality of education. For this reason, skills are needed that are not only based on academic abilities but also non-academic abilities which are soft skills. One of the soft skills abilities is public speaking. Public speaking is very important to instill in students, especially students of Islamic religious education. This qualitative research method uses a library research approach. Data collection techniques using library materials. The results of this study indicate that PAI students who master the soft skills of public speaking greatly affect the quality of education in the future. Therefore, public speaking soft skills are very important for students to master. This ability is very useful for improving the quality of education because a good education is produced by quality students.